Moderate Increase in TCO2 Enhances Photosynthesis of Seagrass Zostera japonica, but Not Zostera marina: Implications for Acidification Mitigation - Miller, Cale A.; Yang, Sylvia; Love, Brooke A. (Frontiers in Marine Science, 2017)
Photosynthesis and respiration are vital biological processes that shape the diurnal variability of carbonate chemistry in nearshore waters, presumably ameliorating (daytime) or exacerbating (nighttime) short-term acidification events, which are expected to increase in severity with ocean acidification (OA). Biogenic habitats such as seagrass beds have the capacity to reduce CO2 concentration and potentially provide refugia from OA. Further, some seagrasses have been shown to increase their photosynthetic rate in response to enriched total CO2 (TCO2). Therefore, the ability of seagrass to mitigate OA may increase as concentrations of TCO2 increase. In this study, we exposed native Zostera marina and non-native Zostera japonica seagrasses from Padilla Bay, WA (USA) to various levels of irradiance and TCO2. Our results indicate that the average maximum net photosynthetic rate (Pmax) for Z. japonica as a function of irradiance and TCO2 was 3x greater than Z. marina when standardized to chlorophyll (360 ± 33 μmol TCO2 mg chl-1 h-1 and 113 ± 10 μmol TCO2 mg chl-1 h-1, respectively). Additionally, Z. japonica increased its Pmax ~50% when TCO2 increased from ~1770 to 2051 μmol TCO2 kg-1. In contrast, Z. marina did not display an increase in Pmax with higher TCO2, possibly due to the variance of photosynthetic rates at saturating irradiance within TCO2 treatments (coefficient of variation: 30–60%) relative to the range of TCO2 tested. Our results suggest that Z. japonica can affect the OA mitigation potential of seagrass beds, and its contribution may increase relative to Z. marina as oceanic TCO2 rises. Further, we extended our empirical results to incorporate various biomass to water volume ratios in order to conceptualize how these additional attributes affect changes in carbonate chemistry. Estimates show that the change in TCO2 via photosynthetic carbon uptake as modeled in this study can produce positive diurnal changes in pH and aragonite saturation state that are on the same order of magnitude as those estimated for whole seagrass systems. Based on our results, we predict that seagrasses Z. marina and Z. japonica both have the potential to produce short-term changes in carbonate chemistry thus offsetting anthropogenic acidification when irradiance is saturating.